Monitoring on Portable Baby Incubator Based on Microcontroller and Notification Using Short Message Service (SMS) - Muhammad Irmansyah; Efrizon Efrizon; Era Madona; Anggara N (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2021)
Portable incubator was one solution to help the premature baby. In general, the baby in the incubator is monitored by the observer manually. This research aimed to apply a microcontroller, temperature sensor, weight sensor, heart rate sensor, and GSM module to monitor and notify the premature babies' condition in portable incubators. The observation can be done by reading the display on LCD and SMS. The hardware used consists of a DS18B20 sensor, Load Cell, Pulse Heart Rate Sensor, Buzzer, LCD, and SIM800L Module. The results showed that the Pulse sensor and DS18B20 sensor could measure and detect the baby's heart rate body temperature and are displayed on the LCD with an average error of 4.354% and 1.437%. The loadcell sensor can detect weight with an error of 2.16%. The duration of sending SMS to Smartphone is 8s for each delivery. SMS was sent if the patient's conditions were weak and critical. Hopefully, these monitoring and notification tools can inform the baby's state in the incubator immediately.